Knowledge, attitudes and practices during the second wave of COVID-19 outbreak: a cross-sectional study from various perspectives - Armin Šljivo; Sutanay Bhattacharyya; Ahmed Mulać; Arian Abdulkhaliq; Sahatçiu Rexhep (Medicinski glasnik, 2021)
Aim: To investigate knowledge, attitudes and practice towards COVID-19 among selected population. Methods: An anonymous online questionnaire based on a Chinese study was distributed via online social media platforms among general population of Bosnia and Herzegovina, Germany, India, Kosovo and Romania. Results: In total 1032 subjects, predominately females, 615 (59.6%) with a mean age of 31.23±12.94 years, single, 705 (68.3%), with high school degree or lower, 469 (45.4%), students, 528 (51.1%) and living in an urban environment, 824 (79.8%), have completed the survey. The median knowledge score was 10.0 (range 0-12). Being male (?: -0.437; p=0.003) and older (?: -0.028; p<0.001) were associated with lower knowledge scores, while being single (?: 1.026; p<0.001) and mental labour employee (?: 0.402; p=0.032) were associated with higher knowledge scores. The vast majority of subjects had not visited crowded places, 630 (61.0%) and wearing masks when they were going out, 928 (89.9%). Being female (OR=0.731; p=0.022), having higher knowledge scores (OR=0.929; p=0.017) and being a mental labour employee (OR=0.713; p=0.031) decreased the exposure to crowded places. High school or lower education level (OR=0.616; p=0.024) decreased the action of wearing a mask in public places, while higher knowledge scores (OR=1.112; p=0.013) increased it. Conclusion: Our study suggests that residents of the selected regions have had good knowledge, pessimistic attitudes and relatively appropriate practices towards COVID-19 during the second wave of the outbreak.
Keywords: attitude; COVID-19; epidemiology; knowledge; public health